2022
DOI: 10.1097/mph.0000000000002588
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019 in Pediatric Oncology Patients: A Matched–Cohort Analysis of the SCCM Discovery Viral Infection and Respiratory Illness Universal Study COVID-19 Registry

Abstract: Background: There is a paucity of multicenter data describing the impact of coronavirus disease 2019 on hospitalized pediatric oncology patients. Using a large, multicenter, Society of Critical Care Medicine (SCCM) Discovery Viral Infection and Respiratory Illness University Study (VIRUS) database, we aimed at assessing outcomes of COVID-19 infection in this population. Method: This is a matched-cohort study involving children below 18 years of age hospitalized with COVID-19 between March 2020 and January 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The database searches yielded 5183 records, of which 3081 were screened following deduplication. We retrieved 56 full‐texts for further screening, of which 12 observational studies were included for analysis (N = 18 024) 22–33 . A list of studies excluded during the full‐text screening phase can be found in Data S1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The database searches yielded 5183 records, of which 3081 were screened following deduplication. We retrieved 56 full‐texts for further screening, of which 12 observational studies were included for analysis (N = 18 024) 22–33 . A list of studies excluded during the full‐text screening phase can be found in Data S1.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 12 included studies, reviewers judged 9 to have a high risk of bias 22,24,26,28–33 . The most frequent source of potential bias in these studies was related to the insufficient adjustment of important confounders in their multivariable regression models.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations